Television News as an Information Source and Its Perception in Slovakia - Višňovský, Ján; Greguš, Ľuboš; Mináriková, Juliána; Kubíková, Karina (Communication Today, 2025)
Television news reporting is one of the most significant information sources, through which the media audiences get acquainted with the current affairs related to all aspects of social life in order to understand them. The research study focuses on the issue of news perception and its interpretation by the recipients with emphasis put on acquiring new information. The theoretical outlines of the study reflect on specific demands and expectations of the society associated with TV news, as well as on today’s television audiences, the process of news perception and its determinants. The authors also offer results of their own research inquiry into television news reporting that aim to define the meaning of news in terms of everyday lives of its recipients, stressing out its information and educational function bound to social demands associated with media. This topic is also related to the recipients’ ability to ‘decode’ pieces of news and acquire the necessary information. The research was conducted by combining various research methods and tools – focus groups, standardised questionnaire surveys and a quantitative content analysis of selected news stories (in total 120 respondents were involved). The researchers used the selected research material consisting of news stories broadcast by Slovak commercial television station TV Markíza to examine the respondents’ ability to interpret news coverage with regard to its function as an information source.